Financial Management for Teens : Building Good Financial Habits Money Moves : Teen Tips for Building your Financial Future - Herman Callo; Wa Ode Rayyani; Muh. Syarif Ahmad; Zalkha Soraya; Risma Risma; Khairunna Istiqamah Halim (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2025)
Although financial management is a vital life skill, many teenagers lack the knowledge and habits to make good financial decisions. This program aims to fix this by giving teens practical financial management skills and encouraging forward-thinking attitudes toward money.The primary goal is to help participants understand fundamental financial concepts such as budgeting, saving, investing, and debt management. To ensure engagement and practical application, the program uses a mixed-methods approach by incorporating workshops, interactive activities, and real-life case studies. Key findings show that participants' capacity to create budgets, save regularly, and make wise financial decisions significantly improved after completing the program. Additionally, the seminars raised awareness of the significance of financial planning for long-term objectives like business or higher education.This effort has broad ramifications as it helps create a generation of financially educated people who are better equipped to handle financial difficulties and take advantage of opportunities in the future. Similar initiatives in communities and schools throughout the world can be built around this paradigm.